Study, Analysis and Implementation of Air-Fuel Ratio Control on Perodua Viva for Better Fuel Consumption - Mohamad Ikhwan Bin Kori, Mohamad Ikhwan (Universiti Teknologi Petronas, 2010)
This project is about the usage of piggyback engine control unit (ECU) to tune the engine in order to obtain the lowest fuel consumption by running in lean combustion. Air-fuel ratio can be defined as the ratio of mass of air to the mass of fuel that is used in combustion process. The air-fuel ratio of a chemically ideal combustion is 14.6:1. The air-fuel ratio setting of vehicle especially that is using electronic fuel injection is controlled by a device called engine control unit (ECU). In order to obtain smaller fuel consumption for Perodua Viva, a leaner air-fuel ratio setting should be used (more than 14.6:1) but the original ECU cannot change the default value set by the manufacturer easily.